Маркетинг корпорацій - Кузьмін, О. Є.; Мукан, О. В. (Видавництво Національного університету «Львівська політехніка», 2003)
Розглянуто питання маркетингової політики корпорації. Визначено керівника корпоративної служби маркетингу, підрозділи та служби, які реалізовують основні функції маркетингу в акціонерній компанії. Запропоновано основні шляхи удосконалення функціонування маркетингової служби корпорації. Зокрема мова йдеться про Інтранет. The problem of corporation marketing policy is considered in the article. The leader of corporate marketing service subsections and subsections, which fulfill basic functions of marketing in the stock association, have been determined. Basic ways of functioning improvement of marketing service of corporation are offered. In particular the article deals with Intranet.